Sub-10 fs pulse characterization using spatially encoded arrangement for spectral phase interferometry for direct electric field reconstruction. - Wyatt, A; Walmsley, I; Stibenz, G; Steinmeyer, G (2006)
We demonstrate an extremely accurate method for measuring ultrabroadband, sub-10 fs pulses even if they exhibit a highly modulated spectrum, space-time coupling, or both. The method uses a spatially encoded arrangement for spectral phase interferometry for direct electric field reconstruction, which allows a zero additional phase measurement to be performed with a relatively low signal-to-noise ratio in real time and single shot.